A modification of superficial properties of materials by means of application of multiple coatings for their use in orthopaedics - Vyrva, Oleg; Zykova, Anna; Safonov, Vladimir; Malyshkina, Svitlana; Lukyanchenko, Volodimir; Valkovich Yadvihа; Rogowska, Renata; Yakovin, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article analyses studies of surface parameters of different multiple coatings, such as: TiN, CrN, (Ti,Cr)N, TiN/TiC10N90, TiN/TiC20N80, which are applied by the arc method (Arc-PVD) on stainless steel samples (1H18N9), and the same coatings with an additional oxide layer Al2O3, which are deposited by the method of reactive magnetron sputtering (RMS method). A comparative analysis of the thickness, roughness and structural characteristics of surfaces was carried on. Other parameters, such as surface wettability (water receptivity / water repellency), surface free energy (SFE) and fractional polarity, were determined by methods of Wu, Owens-Wendt-Rabel-Kaelble, Van Oss and Fowkes. In order to make a further conclusion about an effect of the above factors on biological objects, in vitro experiments were carried out for studying relationships between cell structures and the material in fibroblast cultures. The results show some correlation between the surface properties of the materials and adhesion and proliferation of the cell cultures. Better biological parameters of the response (the total number of cells, proliferation, morphology of cells) were received in case of coatings with higher values of the polar components of SFE and fractional polarity.